Mothering, Habitus and Habitat: The Role of Mothering as Moral Geography for the Inequality Impasse in Urban Education - Talja Blokland (Tijdschrift voor economische en sociale geografie, 2023)
Following Bourdieu, residential location as habitat may provide spatial profit when it matches with a habitus – but how? How can we conceptualize situations of mismatch between habitat and habitus, and what may they mean for urban inequalities? This article explores this topic through the lens of mothering practices in elementary schools. Qualitative interviews in two neighbourhoods in Berlin, Germany, suggest how moral geographies at intersections of class and race/ethnicity structure parents' opportunities to organize resources for children in their specific spatial contexts. It argues that mothering practices can help us see not just that, but how habitus and habitat are related. Empirically, it suggests that the moral geographies in which these schools are embedded reinforce the exclusionary consequences of their institutional practices. I theorize that the moral geographies of neighbourhoods as sites of mothering practices vis-à-vis the class-based state logics in institutions may contribute to an urban impasse of educational inequality.
Keywords: 330; Moral geography; mothering; parents; urban education; Berlin; qualitative interviews